IOT-DRIVEN SMART KITCHEN: ENHANCING NUTRITIONAL VALUE THROUGH REAL-TIME FOOD MONITORING AND FEEDBACK SYSTEMS (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The IoT-driven smart kitchen represents a cutting-edge integration of technology and culinary practices aimed at enhancing nutritional quality and cooking efficiency. This system utilizes real-time monitoring and feedback mechanisms to optimize food preparation processes, ensuring that meals are prepared with minimal nutrient loss. Key components of the smart kitchen include temperature and humidity sensors, nutrient degradation monitors, and ingredient freshness trackers, all of which work together to maintain ideal cooking conditions. The system’s user interface, featuring visual dashboards, interactive recipe guides, and voice-assisted feedback, facilitates a seamless cooking experience by providing real-time data and personalized recommendations. This design not only simplifies complex cooking tasks but also helps users make healthier food choices. The impact of the smart kitchen system on nutritional value is significant, with studies showing improved retention of essential vitamins and minerals compared to traditional cooking methods. Additionally, user satisfaction surveys reveal that the system enhances cooking efficiency and confidence, with many users appreciating the system’s ability to tailor recommendations based on individual dietary needs. The long-term benefits of using the smart kitchen system include a shift towards healthier eating habits and better management of dietary goals, such as reduced sodium intake and increased fiber consumption. However, the study also identifies areas for improvement, such as enhancing compatibility with older appliances and refining the user interface to reduce overwhelming notifications. Overall, the smart kitchen system represents a promising innovation in the realm of home cooking and nutrition, offering a practical solution for those seeking to improve their dietary habits and overall well-being. As technology continues to advance, future iterations of the system are expected to further refine these capabilities, making the smart kitchen an integral part of modern culinary practices.